PERSPEKTIF DEEP ECOLOGY ARNE NAESS DALAM MENILAI DAMPAK LINGKUNGAN IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 26 TAHUN 2023 TENTANG PENGELOLAAN HASIL SEDIMENTASI DI LAUT - Dewi, Nashwa Fadila; Trialika Putri, Andiani; Khairunnisa, Fadlah; Ramadina, Aliyana Farha (Gapenas Publisher, 2024)
The point of this write-up is to dive into Arne Naess's Deep Ecology perspective on the environmental impact of implementing Government Regulation No. 26 of 2023 about managing sedimentation products in the sea. It's based on qualitative research using a normative juridical approach through a literature review. The analysis shows that the policy still leans heavily on an anthropocentric view, prioritizing economic benefits for humans. Naess's Deep Ecology argues that this approach doesn’t give enough attention to ecosystem balance and environmental sustainability. Extracting sea sand has major consequences for biodiversity, marine habitats, and can worsen environmental damage while creating social problems.